Knowledge, attitudes, and practices regarding rabies in Grenada - Glasgow, Lindonne; Worme, Andre; Keku, Emmanuel; Forde, Martin (PLOS Neglected Tropical Diseases, 2019)
Author summary About 62% of households in Grenada owned animals that are susceptible to rabies. Pets, particularly dogs, were more commonly owned than livestock. Males were more likely to correctly identify animals that are susceptible to rabies. The level of participation in the animal vaccination program was low, especially among owners of livestock. A lack of knowledge about the free anti-rabies vaccination service and the length of time that it took to vaccinate animals were the most common problems associated with the low vaccination rate. Increasing education programs, controlling the mongoose population, and increasing the vaccination times per year were the most frequent recommendations to improve the Ministry of Health rabies control programs. The anti-rabies program remains a critical step to maintain the current zero-human-case status in Grenada. There is a need to also expand the vaccination program and increase the rate of animal vaccination.